The Effect of an Essential Oil Mix Derived from Oregano, Clove and Anise on Broiler Performance - Ertas, Osman Nihat; Guler, Talat; Ciftci, Mehmet; Dalkilic, Bestami; Simsek, U. Gulcihan (International Journal of Poultry Science, 2005)
This study was conducted to explore the usage of essential oil mix (EOM) in broiler nutrition as a natural growth promoting substance instead of antibiotics. Different levels of EOM were added to a standard diet, to determine its effect on feed intake, daily live weight gain and feed conversion ratio compared to control and antibiotic groups. Two hundred and fifty five day-old broilers (Ross-308, n = 250) were divided into five equal groups were as follow: Control group (no EOM or antibiotic), 100 ppm EOM group , 200 ppm EOM group, 400 ppm EOM group with and an Antibiotic group (0.1% Avilamycin). The diets were prepared freshly each day. Experiment carried out 35 days. The feed intake was similar between the groups (p>0.05), but the highest daily live weight gain was observed in the 200 ppm EOM group (71.31 g) followed by Antibiotic group (65.84 g), 100 ppm EOM oil group (63.40 g), control group (61.30 g) and 400 ppm EOM group (61.17 g). Thus, daily live weight gain increased in 200 ppm EOM group by approximately 16 % over the control group and approximately 8 % over the antibiotic group. Feed conversion ratio was improved in 200 ppm EOM group by approximately 12 % over the control group and approximately 6 % over the antibiotic group. The results show that, EOM could be considered as a potential natural growth promoter for poultry.